Progressive Freeze Concentration of Coconut Water and Use of Partial Ice Melting Method for Yield Improvement - J. A. E. C. Jayawardena; M. P. G. Vanniarachchy; M. A. J. Wansapala (International Journal of Food Science)
Coconut water is a highly nutritious liquid food which is a by-product of the desiccated coconut industry. Freeze concentration is the most suitable concentration method for coconut water since the low-temperature operation for concentration does not deteriorate the original quality of coconut water. Suspension freeze concentration (SFC) and progressive freeze concentration (PFC) are the available FC methods, and SFC is a complex and expensive method compared with PFC. PFC is a novel freeze concentration technique to concentrate liquid food by using a simple system. The limitation of PFC is the lower product yield than SFC, and to overcome the problem, the partial ice-melting technique can be used. A simple cylindrical apparatus was used for PFC which consists of a sample vessel, agitator system, and a cooling bath (at −23°C±2°C temperature). The final concentration of the liquid product was directly affected by the apparatus agitator speed and sample vessel dipping speed. PFC agitator speed of 290 rpm and dipping speed of 1.3 cm h-1 were reported as the optimum operating conditions to achieve the highest concentration for the PFC apparatus used in this study. Using optimized agitation speed and dipping speed, coconut water was concentrated up to Brix 8.5° from the initial concentration of Brix 3.5°. PFC coconut water achieved 73.56% of total yield, 2.42 of concentration ratio, 0.7° of ice phase concentration, and 0.08 of effective partition coefficient. The partial melting technique was successfully explored by recovering initial ice fractions with high solute concentrations, and the total yield was improved up to 80%.